Book Reviews (The Muslim world, 1930)
Book reviewed in this article: The History of Hayy Ibn Yaqzan. By Abu Bakr Ibn Tufail: Translated from the Arabic by Simon Ockley: Revised with an introduction by A. S. Fulton. Chapman and Hall Ltd., London, 1929. pp. 181. 21/-. Attitudes to Other Faiths. By Daniel J. Fleming, Ph.D. Association Press, 347 Madison Avenue, New York. pp. XX & 166. USD1.76. The Koran Translated Into English from the Original Arabic. By George Sale with explanatory notes from the most approved commentators and with an Introduction by Sir Edward Denison ROSS. C.I.E., Ph.D., etc. Warne & Co., London and New York. pp. 608. 10/6. Christ Islam. By Rev. James Robson, M.A. John Murray, London. pp. 128. Prim 3/6. Le Coran. Traduction nouvelle par Edouard Montet. Professeur de langues orientales. Recteur honoraire de l'Université de Cenève. Payot, 106 Boulevard Saint Germain. Park 1 vol. 8vo. 896 pp. 76 frs. The Islamic Book. A Contribution to its Art and History from the Seventh to the Eighteenth Century. By Sir Thomas Arnold and Professor Adolph Grohmann. The Pegasus Press. £9.9.0. Aggrey of Africa, A Study in Black and White. By E. W. Smith, Student Christian Movement, 1929. pp. 292. 7/6. The Zoological Section of the Nuzhat al-Qulob of Hamdullah al-Mustaufl al-Kazwini: edited, translated and annotated, by Lieut.-Col. J. Stephenson. London. 1928. 8vo. xix. 100. 127 pp. Royal Asiatic Society. (74 Crosvenor Street, London, W.1.) L'Arabie occidentale avant l'Hégire. par H. Lammens. Beirut, 1928. 8vo. iv, 344 pp. Imprimérie Catholique. Fallen Angels in Jewish, Christian and Mohammedan Literature. By Rabbi Leo Jung, Ph.D. The Dropsie College, Philadelphia. pp. 165. Christianity and some living Religions of the East. By Sydney Cave, M.A., D.D. Duckworth, London. 222 pp. 5s. Seventy Years. A Short History of the British Syrian Mission from 1860 to 1930. By J. D. Maitland-Kirwan, British Syrian Mission, London. S. W. I., pp. 96. Le Sahara. By E. F. Gautier, with 36 illustrations and maps. Payot. Paris. 24 fr. Al-Babn'l-Hadi'Ashar: a Treatise on the Principles of the Shi'ite Theology. By Hasan b. Jusuf ‘All Ibnu’ l-Mutahhar Al Hilll with commentary by Miqdad-i-Fadil Al Hilli—Tranelated from the Arabic by William McE. Miller, M.A., B.D., London, Royal Asiatic Society. pp. xiv and 104. The Heart of Libya. By G. E. Simpson. H. F. & G. Witherby, London. pp. 207. 7s. 6d. net. Zaka Ullah of Delhi. By C. F. Andrews. W. Heffer and Sons, Cambridge. pp. 166, 7s. 6d. Mélanges d'Histoire des Religions. Par H. Hubert et M. Mauss. Felix Alcan, Paris. pp. 236. Grundsteine zu einer Mittelländisch-Asianischen Urgeschichte. By Dr. J. Karst. Otto Harrassowitz, Leipzig. pp. 247, price 20m. L'Hellénieme et l'Egypte moderne. By Ath. G. Politis. Paris, Alcan, 630 pp. 50 francs. l'algérie. Par Augustin. Bernard, professeur de Géographie et Colonisation de l'Afrlqué du Nord à la Faculté des Lettres de Paris. Librairie Felix Alcan, 108 Boulevarde Saint Germaine VIe Paris, 1929. 522 pp. Die Turkel seit dem Weltkriege: Geschichtsakalendar, 1918–28, von Gotthard Jäschke und Erich Pritsch. Berlin, 1929. 8vo. 154 pp 6 Mk. Deutsche Gesellschaft für Islamkunde. A History of Nationalism in the East. By Hans Kohn. Routledge, London, 1929. pp. 476, 26 s. Agricultural Afghanistan. By Prof. N. I. Vavilov and D. D. Bukinich. Institute of Applied Botany, 1929. Leningrad. pp. 610 and 75. Jérusalem musulmane d'apès Max Van Berchen. By Gaston Migeon. Paul Geuthner, Paris.